DEVELOPMENT AND CHARACTERIZATION OF NOVEL HERBAL FORMULATION (POLYMERIC MICROSPHERES) OF SYZYGIUM CUMINI SEED EXTRACT - Biswas, Ranu; Sen, Kalyan Kumar (International Journal of Applied Pharmaceutics, 2018)
Objective: The purpose of the present investigation was to develop and characterize a novel herbal formulation (polymeric microspheres) of Syzygium cumini seed extract. Methods: The extract-loaded microspheres using biological macromolecule ethyl cellulose (EC) was prepared by o/w emulsion solvent evaporation technique using polyvinyl alcohol (PVA) emulsifier. The effect of various process and formulation variables (stirring speed, evaporation time, drug/polymer ratio and organic/aqueous phase ratio) on the properties of microspheres was evaluated. Results: Micromeritic properties indicated good flow properties, and scanning electron microscopy (SEM) confirmed the spherical nature of the prepared microspheres. The particle size and entrapment efficiency were varied between 34.25 to 176.25 Âµm and 10.51 to 42% depending upon the variables. All the formulations showed minimal drug release in an acidic environment (pH 1.2) confirming the prevention of drug release in the stomach and enteric nature of the polymer. Sustained drug release has been observed in alkaline dissolution media (pH 7.4) after 12 h of drug release study except for formulation F7 which contains a lower concentration of polymer. The fourier transform infrared spectroscopy (FTIR) analysis indicated the compatibility of the extract with the polymer. The absence of extract-polymer interaction was indicated by the differential scanning calorimetry (DSC) thermogram. x-ray diffraction (XRD) analysis revealed the amorphous nature of the extract in the microspheres which in pure form exhibits a crystalline structure. Conclusion: The findings of this present study suggest that microsphere formulation was a promising carrier for novel delivery of herbal drugs.